Developing Review Websites Using Feature Driven Development (FDD) - Marchelin Fau Hariono; Albert Albert; Arvin Vinsensius; Adhi Kusnadi (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2014)
In this paper discussed a case study of the development of a website review . The discussion of this case study is limited to the implementation and use of the five steps in the development FDD review website . Moreover it is not a discussion of such budget , personal develomnent , the success rate of software , and others . That reviews are steps in the development of the system , ie develop an overall model of phase , build a feature list , plan by features , design by features , build by feature . Conclusions that can be drawn from this discussion is the Feature Driven Development successfully used for software development carried out by the team , which will produce a good system . FDD will also make the user comfortable , where there is an attractive feature to assist companies in doing business . FDD does not focus on how to design a system that is considered costly and time. However , FDD prioritize how to execute a project with a faster and more efficient despite the implementation of the use of this method requires a lot of qualified human resources. Index Terms - website review, feature driven development, FDD